MVA-HBVac—A novel vaccine vector that allows pan-genotypic targeting of hepatitis B virus by therapeutic vaccination - Anna D. Kosinska; Martin Kächele; Helene A. Kerth; Martin Mück-Häusl; Edanur Ates Öz; Merve Gültan; Lea Hansen-Palmus; Julia Sacherl; Chunkyu Ko; Julia Festag; Michael H. Lehmann; Carolin Mogler; et al. (Molecular Therapy: Nucleic Acids)
Therapeutic vaccination holds the promise to cure chronic hepatitis B virus (HBV) infection. We hypothesize that B cell, CD4, and CD8 T cell responses are necessary to overcome HBV-specific immune tolerance in chronic infection because they accompany the rare, spontaneous resolution of chronic HBV infection. Therefore, we designed the heterologous prime-boost vaccine TherVacB in which virus-like particle vaccination stimulates B and helper CD4 T cells and primes cytotoxic effector CD8 T cells and a vector boost expands the T cell response. Here, we report the generation and characterization of a novel modified vaccinia virus Ankara (MVA)-based vector, MVA-HBVac, capable of inducing strong and multi-specific T cell responses against the immunodominant epitopes of four different viral proteins covering >95% of HBV strains circulating worldwide. When MVA-HBVac was administered after a prime with adjuvanted hepatitis B S- and core-antigens forming virus-like particles, it activated strong HBV-specific CD4 and CD8 T cell responses against the major HBV antigens in vivo in naive and HBV carrier mice. This induced a sustained antiviral effect against different, clinically relevant HBV genotypes. Our data showed that the TherVacB regimen employing the novel, pan-genotypic MVA-HBVac vector could overcome HBV-specific immune tolerance and lead to the initiation of clinical trials evaluating the therapeutic vaccine.